Improving Learning Outcomes of Basic Pencak Silat Crescent Kick Techniques Using Learning Vertical Electric Jump Media For 5th Grade Male Students of Assalaamah Elementary School in 2025 - Candra, Juli; Natas P, Ahmad muchlisin (JUPE : Jurnal Pendidikan Mandala, 2025)
A This study aims to improve the learning outcomes of basic roundhouse kick techniques among male students in grade 5 at IT Assalaamah Elementary School in 2025. The problem often encountered is the low mastery of roundhouse kick techniques, which is caused by conventional learning methods that lack variety and appeal. This study uses the Vertical Jump Elektrik learning media as an innovation to improve students' coordination, balance, and leg strength, which are important elements in the scissor kick. The research method used is Classroom Action Research (CAR). The research subjects are male students in grade 5 at SD IT Assalaamah. Data were collected through observation, practical tests, and documentation. The results showed a significant improvement in learning outcomes for the crescent kick. In cycle I, the average score of the students was still low at 63.35, but after the Vertical Jump Elektrik media was implemented, the average score in cycle II increased dramatically to 77.81, reaching the expected score. The use of the Electric Vertical Jump learning media was effective in improving the learning outcomes of basic pencak silat crescent kick techniques among 5th grade male students at SD IT Assalaamah by 14.71.